Procedimento autônomo da tutela antedipada: uma análise das tutelas requeridas em caráter antecedente nas Varas Cíveis da Comarca do Recife-PE. - Melo, Danilo Gomes de (2023)
This doctoral thesis investigates the effectiveness and procedural inadequacies of the anticipatory injunction sought in an antecedent manner, provided for in articles 303 and 304 of the Brazilian Code of Civil Procedure of 2015 (CPC/2015), a legislative innovation aimed at optimizing the efficiency of judicial proceedings. The study is based on a qualitative empirical research, analyzing cases involving anticipatory injunctions in an antecedent manner in civil courts of the Recife district, in order to assess the practical impact of the procedure and identify obstacles faced in its application. The work addresses the theoretical foundation of provisional reliefs, focusing on the special procedure of anticipatory injunction stipulated in the CPC/2015 and the French référé model, which influenced the Brazilian system. Based on the collected data and considering the theoretical premises developed in the literature review, the research seeks to contribute to the understanding of the practical difficulties faced in the application of the autonomous procedure of the anticipatory injunction sought in an antecedent manner and proposes legislative modifications to make the achievement of its application feasible.